A prospective, randomized, double-blind clinical trial study to evaluate a method for uvular repair during primary palatoplasty. Issue 2 (April 2014) - Rossell-Perry, Percy; Navarro-Gasparetto, Carlos; Caceres-Nano, Evelyn; Cotrina-Rabanal, Omar
Abstract The purpose of this study was to evaluate the efficacy of a new technique for uvular repair in patients with cleft palate. This is a prospective, randomized, double blind controlled trial study with Ethical Committee approval between two groups of 30 patients each with cleft palate who were operated on using the conventional and proposed method of uvular repair from 2005–2007. Data was from the Outreach Surgical Center Program, Lima, Peru. Two groups of 30 patients each with cleft palate were operated on using the new technique by the Outreach Surgical Center Program Lima since 2007. Data collection was accomplished by physical exam to evaluate the appearance of the constructed uvula, as well as the presence or absence of a fistula and by a speech therapist. This comparative study did not find a statistically significant association between the conventional and the proposed method for uvular repair or the presence of postoperative hypernasal speech determined at 1–5 years of age during follow-up (p = 0.640). This study observed no increase in the rate of fistulas and/or VPI between these two groups so it was concluded that the use of the proposed method for uvular reconstruction does not affect the closure of the velopharyngeal sphincter and, thus, the development of VPI is not increased.